Volume Irigasi untuk Budidaya Hidroponik Melon dan Pengaruhnya terhadap Pertumbuhan dan Produksi - Sulistyono, Eko; Riyanti, Halimah (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2015)
ABSTRACTDetermination of the appropriate volume of irrigation is needed in hydroponic systems. The easy and rapid method for determination of volume irrigation should be developed. The research was conducted to determine irrigation volume based on evaporation and to study their effect on melon growth and yield in hydroponic system. The irrigation water volume was determined based on evaporation (E) of the 30 cm diameter pan placed over the crop canopy, and melon (Cucumis melo L.) plant was subjected to four irrigation water levels (0.5, 1.0, 1.5, and 2.0 E) in combination with three periods of irrigation based on plant growth phase ( planting to harvesting; planting to flowering, and flowering to harvesting). At three weeks after planting, irrigation volume of 1.5 E increased plant height as much as 54% compared with irrigation volume of 0.5 E; irrigation volume of 2.0 E increased leaf number as much as 47% compared with irrigation volume of 0.5 E. Melon yield was 2.173 kg per plant by irrigation volume of 2.0 E applied during planting to flowering, increased of 98% compared with irrigation volume of 0.5 E, but it was not significant different with irrigation volume of 1.5 E applied during flowering to harvesting. It is concluded that irrigation volume for hydroponically-grown melon was as much as 1.0 time of evaporation during vegetative phase and 1.5 times of evaporation during generative phase.Keywords: evaporation, sand media, flower number, fruit diameter, fruit weight